Implementasi Penguatan Karakter Disiplin dan Nasionalisme Melalui Ekstrakurikuler Pramuka di SD Negeri Gemolong Kabupaten Sragen - Wahyuni, AryawatiTuti, Drs. Saring Marsudi, SH. M.Pd (2016)
The purpose of this study was to determine 1) the implementation of extracurricular scout in SD Negeri Gemolong, 2) any person who participated in implementing extracurricular scout in SD Negeri Gemolong, 3) the function of the implementation of extracurricular scout in SD Negeri Gemolong, 4) the content of the character values of discipline and Nationalism in the implementation of extracurricular scout in SD Negeri Gemolong, 5) barriers in the implementation of extracurricular scout in SD Negeri Gemolong in applying disciplinary character and Nationalism in children. This type of research is based on a qualitative approach with a qualitative descriptive research. This research was conducted in SD Negeri Gemolong, with a research subject of students of class III, IV, and V. The data collection techniques used were observation, interviews, field notes, and documentation. The validity of the data using triangulation data source. Data analysis technique used is an interactive model. Based on the research that has been done can be concluded that strengthening implementation code of discipline and Nationalism Through extracurricular Scouts in elementary school Gemolong Sragen held by their subservience and obedience to all applicable regulations, have the national spirit and love for the land Air Indonesia indicated the various a positive attitude. Characters in extracurricular activities scout discipline shown by students in coming accuracy or perform a given task, orderly in the regulation is to dress neatly and complete corresponding provisions, and have discipline in small things that dispose of waste in place. Characters nationalism indicated the willingness of students to participate and the spirit of the flag-raising ceremony every Monday, singing songs of National nor area, study hard, get to know the various heroes that exist in Indonesia, understood and memorized the Pancasila as the symbol of the State, speak Indonesian, have a good concept of nationalism and patriotism ditujukkan with concern for the environment. Strengthening discipline code and Nationalism in extracurricular activities conducted through exemplary scout, attitude example, habituation, learning, assignments, as well as with educational games. Additional values that appear when the observation takes place is hard work, honesty, self-contained, self-confident, polite, democracy, and concern. In the implementation of the character strengthening discipline and nationalism through extracurricular scout there are various obstacles that make implementation of extracurricular less optimal that students feel when the following conditions of extracurricular scouts, coaches scout, as well as from parents